Identification of Periplakin as a New Target for Autoreactivity in Idiopathic Pulmonary Fibrosis - Taillé, Camille; Grootenboer-Mignot, Sabine; Boursier, Céline; Michel, Laurence; Debray, Marie-Pierre; Fagart, Jérôme; Barrientos, Lorena; Mailleux, Arnaud; Cigna, Natacha; Tubach, Florence; Marchal-Sommé, Joëlle; Soler, Paul; et al. (American journal of respiratory and critical care medicine, 2011)
Injury to alveolar epithelial cells is central to the pathophysiology of idiopathic pulmonary fibrosis (IPF). An abnormal autoimmune response directed against antigens of the alveolar epithelium may contribute to the disease. To detect circulating autoantibodies (autoAbs) directed against epithelial structures. We performed immunoblot by separating human placental amnion extract or alveolar epithelial cell (A549 cell line) proteins on polyacrylamide gels, blotting on nitrocellulose membranes, and incubating with serum from patients with IPF (n = 40) or healthy subjects (n = 40). Proteomic analysis and mass spectrometry characterized the target protein. Inhibition experiments performed with the correspondent recombinant protein confirmed our results. We identified IgG autoAbs recognizing a 200-kD protein in the serum of patients with IPF. Proteomic analysis identified this protein as human periplakin (PPL), a component of desmosomes. Anti-PPL Abs were found by immunoblot in both serum and bronchoalveolar lavage in patients with IPF: 16/40 (40%) of them were positive versus none of the control subjects. Immunohistochemistry revealed that PPL was strongly expressed in bronchial and alveolar epithelium, but that PPL exhibited changes in intracellular localization among normal and fibrotic alveolar epithelium. In an alveolar epithelial wound repair assay, an anti-PPL IgG decreased cell migration. Recombinant PPL induced bronchoalveolar lavage T lymphocyte proliferation. Patients with IPF with anti-PPL Abs had a more severe respiratory disease, despite no difference in survival. We found a new circulating autoAb directed against PPL in patients with IPF, associated with a more severe disease.